Use of NH3 fuel to achieve deep greenhouse gas reductions from US transportation - Doo Won Kang; John H. Holbrook (Energy Reports, 2015)
The transportation sector is one of the largest sources of greenhouse gases (GHGs) emissions in the United States. This study identifies scenarios for dramatically reducing future GHG emissions from the US transportation sector, specifically from light-duty vehicles (LDVs), by phasing in ammonia (NH3)-fueled vehicles in place of vehicles using petroleum-based fuels. Projected US LDV carbon dioxide (CO2) emissions from the Annual Energy Outlook (AEO) 2013 reference case projections prepared by the United States Department of Energy serve as the reference case for this study. Two scenarios, in addition to the AEO reference case, have been developed in this study to illustrate the GHG emissions mitigation potential of implementing NH3-fueled vehicles in the US LDV transportation sector through 2040. This study uses the software tool LEAP (the Long range Energy Alternatives Planning System), with which alternative scenarios can be created and evaluated by comparing their energy requirements and environmental impacts. Aggressive implementation of NH3-fueled vehicles replacing gasoline vehicles to account for 100% in 2040 achieves reduction of about 30% of the cumulative LDV CO2 emissions from 2010 through 2040 produced in the reference case. It eliminates most of the annual LDV CO2 emissions projected in the reference case in the year 2040, with a 96% reduction from reference case levels, equivalent to a reduction of approximately 718 million metric tons CO2 equivalent in that year's emissions. The current study demonstrates that NH3-fueled vehicles could be a promising near-term alternative for LDV because of its significant contribution in reducing CO2 emissions compared with vehicles of carbon based fuels.
Keywords: 330; NH3-fueled vehicles; emissions; Global warming; LEAP